Poverty, hunger, and malnutrition: Challenges and breakthroughs for rural revitalization - Kharas, Homi; Noe, Lorenz (International Food Policy Research Institute, 2019)
The first two Sustainable Development Goals call to end poverty, hunger, and malnutrition by 2030. This chapter looks at trends in rural poverty, hunger, and malnutrition, and the potential to put the world on course to meet these SDGs. The global rural poverty rate is currently 17 percent; the urban poverty rate is 7 percent. Rural areas lag behind in reducing the prevalence of child stunting and underweight among children. Investment in food and nutrition security is insufficient to address these problems, and the international trade and investment climate increases the challenge. Breakthroughs will require not only greater investment but also better data and a systems approach to addressing rural needs that integrates natural resources and other critical sectors. A systemwide transformation and revitalization is needed to raise rural incomes, improve rural food security and nutrition, safeguard environmental resources, and lift living conditions in rural areas.